2015
DOI: 10.1111/jbi.12465
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of vertebrates on the Sunda Shelf: a multi‐species comparison

Abstract: 26Aim Pleistocene environmental fluctuations had well-characterized impacts on the 27 patterns of within-species divergences and diversity in temperate habitats. Here we 28 examine the impact the Pleistocene had on widely distributed forest vertebrates in a 29 tropical system where the distribution of the habitat was affected by those 30 fluctuations. 31Location Sundaland, tropical Southeast Asia. 32Methods We conducted a comparative phylogeographical analysis of 28 non-33 migratory, forest-dependent vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
5
43
1
1
Order By: Relevance
“…According to Leonard et al . (), within‐species divergences in 28 Southeast Asian bird and rodent species were not caused by a single event but occurred during the course of repeated climatic fluctuations and sea‐level changes. These processes included local extinctions and re‐colonizations during and after the Pleistocene.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Leonard et al . (), within‐species divergences in 28 Southeast Asian bird and rodent species were not caused by a single event but occurred during the course of repeated climatic fluctuations and sea‐level changes. These processes included local extinctions and re‐colonizations during and after the Pleistocene.…”
Section: Discussionmentioning
confidence: 97%
“…In many terrestrial vertebrate species, populations from Sumatra, Java and the Malay Peninsula were identified as closest relatives and were sister to those from Borneo (Fig. a1; Gorog et al, ; Lim et al ., ; Leonard et al ., ) However, the geographical sampling in most studies does not allow identification of the Sundaic‐Indochinese transition zone. Knowledge about the degree of genetic divergence among populations north–south of the Isthmus of Kra is crucial for evaluating potential historical factors that may have influenced a postulated disjunction.…”
Section: Introductionmentioning
confidence: 99%
“…Leonard et al. () compared 28 taxonomic groups across the Sunda Shelf and found that the oldest dispersal event was 3.9 Ma (Pliocene). De Bruyn et al.…”
Section: Discussionmentioning
confidence: 99%
“…Speciation may have resulted from the ecological adaptation of Javan deer Rusa timorensis to the prevailing vegetation type on Java, separating it from its sister species, the subtropical forest‐adapted sambar Rusa unicolor . Java and Bali, although part of Sundaland, had (and still have) different climatic conditions than Sumatra and Borneo and thus allowed differentiation between species based on evolved ecological adaptations (Leonard et al., ). The climate on Java is characterized by a West–East gradient, a transition from a slightly seasonal climate in the West to a strongly seasonal one in the East.…”
Section: Discussionmentioning
confidence: 99%
“…Two major clades were recovered and are indicated by the species names. Haplotypes are described in Table A1 H_39 Borneo and thus allowed differentiation between species based on evolved ecological adaptations (Leonard et al, 2015). The climate on Java is characterized by a West-East gradient, a transition from a slightly seasonal climate in the West to a strongly seasonal one in the East.…”
Section: Discussionmentioning
confidence: 99%